Development of an optimal model for technique. Part 7 - Body base of support for freestyle - Havriluk, R. (Swimming World Magazine, 2019)
Since hand force is directly related to swimming velocity, controlling the arm motion on the push phase during freestyle has great potential for almost every swimmer. Unfortunately, it is a substantial challenge to independently push the hand backward while the torso rotates upward.